STUDENTS' GEOMETRIC THINKING ON TRIANGLES: MUCH IMPROVEMENT IS NEEDED - Joanne Ramirez Casanova; Claudeth Cathleen Canlas Cantoria; Minie Rose Caramoan Lapinid (Jurnal Infinity, 2021)
A look into students’ misconceptions help explain the very low geometric thinking and may assist teachers in correcting errors to aid students in reaching a higher van Hiele geometric thinking level. In this study, students’ geometric thinking was described using the van Hiele levels and misconceptions on triangles. Participants (N=30) were Grade 9 students in the Philippines. More than half of the participants were in the van Hiele’s visualization level. Most students had imprecise use of terminologies. A few had misconceptions on class inclusion, especially when considering isosceles right triangles and obtuse triangles. Very few students correctly recognized the famous Pythagorean Theorem. Implications for more effective geometry teaching are considered.